Internalisasi Nilai-Nilai Karakter melalui Kegiatan Ekstrakulikuler Musik Gambus di MA Fatwa Alim Madiun - Hamam Saeroji , Hamam Saeroji; Sudarmiani, Sudarmiani; Moh Rifai , Moh Rifai (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The phenomenon of final moral degradation is a concern expressed by the father of character education, Thomas Lickona. The development of character values through school culture can be practiced through leadership, exemplary, friendliness, tolerance, hard work, discipline, social care, environmental concern, a sense of nationality, nationalism, and responsibility. The formulation of the problems in this study: Gambus music extracurricular activities at MA Fatwa Alim Madiun, Internalization of character values through extracurricular activities of Gambus Music at MA Fatwa Alim Madiun, and Inhibiting and supporting factors for the internalization of character values through gambus music extracurricular activities at MA Fatwa Alim Madiun. This study aims to describe the internalization of character values that are focused on social character values through Gambus Music's extracurricular activities at MA Fatwa Alim. The research method used is qualitative, with data collection techniques in the form of observation, interviews, and documentation. The results of the study show that the extracurricular activities of gambus music at MA Fatwa Alim not only teach about the art of religious musical instruments but also a process of internalizing the character values of tolerance, responsibility, cooperation, and care for the environment. Character value internalization is through value transformation, transaction, and trans-internalization of character values. At the same time, the inhibiting and supporting factors of the process of internalizing character values are divided into two, namely internal factors and external factors.